Regenerative Endodontics Procedure: An Umbrella Review - Luísa Lopes (International Journal of Environmental Research and Public Health, 2021)
The Regenerative Endodontic Procedure (REP) is a biologically based method in which a damaged pulp–dentin complex is replaced by a new vital tissue. This umbrella review aimed to critically assess the available systematic reviews (SRs) on REP. An electronic database search was conducted (PubMed-Medline, CENTRAL, Scielo, Web of Science, and LILACS) until December 2020. Studies were included if they were an SR on REP. The Risk of Bias (RoB) of SRs was analyzed using the Measurement Tool to Assess SRs criteria 2 (AMSTAR2). The primary outcome was the methodological quality in each specific section of REP protocols and outcomes. From 403 entries, 29 SRs were included. Regarding the methodological quality, ten studies were of critically low, three of low, fourteen of moderate, and two were rated as high quality. The quality of evidence produced by the available SRs was not favorable. Future high standard SRs and well-designed clinical trials are warranted to better elucidate the clinical protocols and outcomes of REP.